Boundary-spanning in school-university partnerships - Zenkov, Kristien; Polly, Drew, 1977-; Rudder, Lin (Research in professional development schools and school-university partnerships, 2024)
This book aims to provide a resource to individuals involved with teaching, teacher education, and teachers' and teacher educators' professional learning (i.e., professional development), exploring the activities and roles of individuals whose primary professional homes are university or PK-12 school settings but who engage in boundary-spanning capacities and tasks. In the context of school-university partnerships as well as teacher education programs, boundary-spanning activities and roles have become more common. Boundary-spanning activities and roles include formal and informal activities and capacities where individuals housed in either universities or PK-12 districts participate in activities in the other settings (NAPDS, 2021). These activities and capacities range from very formal and permanent (outlined in contracts and memoranda of understanding) to very informal and temporary (including one-time, volunteer structures).